(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The water regime of the transboundary Narva River has always been constantly addressed by the hydrometeorological community. For many years, at the interstate level (the Russian Federation and the Republic of Estonia), there has been a discussion about the accuracy of flow assessment and the correctness of the methods applicable for these purposes. In some years, the discrepancies between the estimates of the average annual water discharge obtained by the Estonian and Russian sides reach values of 20-27%. Sustainable, reliable water use requires updating approaches and achieving greater unambiguity in the flow assessment. In the presented article, various sources of uncertainty in the Narva river flow assessment as hydrodynamic, seasonal factors and imperfection of existing methods are considered.